The DNA binding properties of the MutL protein isolated from Escherichia coli. - Bende, S M (1991)
The mutL gene of Escherichia coli, which is involved in the repair of mispaired and unpaired nucleotides in DNA, has been independently cloned and the gene product purified. In addition to restoring methyl-directed DNA repair in extracts prepared from mutL strains, the purified MutL protein binds to both double and single stranded DNA. The affinity constant of MutL for unmethylated single stranded DNA was twice that of its affinity constant for methylated single stranded DNA and methylated or unmethylated double stranded DNA. The binding of MutL to double stranded DNA was not affected by the pattern of DNA methylation or the presence of a MutHLS-repairable lesion.